2012
DOI: 10.5581/1516-8484.20120089
|View full text |Cite
|
Sign up to set email alerts
|

A model of genetic guidance for hemoglobinopathy patients and laboratory diagnosis of family members as educational and preventive measures

Abstract: Background: The high frequency of hemoglobinopathies in Brazil constitutes a public health problem and thus educational and preventive measures are necessary to reduce the incidence. Genetic guidance, a modality of genetic counseling, and family screening are measures that can assist in reproductive decisions and mitigate clinical, psychological and social problems of families with these disorders.Objetive: The objective of the current study was to evaluate the effectiveness of educational and preventive measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…Kılınç emphasised the usefulness of premarital screening programs in the evaluation of haemoglobinopathies in Turkey (7). The need for similar programs was also reported by Ferreira et al (3) in the case of Brazil. The effect of these legal obligations was observed in our study with a dramatic increase of pre-marital testing from 5.1% among couples married before 1994 to 95.0% among those married after 1994.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Kılınç emphasised the usefulness of premarital screening programs in the evaluation of haemoglobinopathies in Turkey (7). The need for similar programs was also reported by Ferreira et al (3) in the case of Brazil. The effect of these legal obligations was observed in our study with a dramatic increase of pre-marital testing from 5.1% among couples married before 1994 to 95.0% among those married after 1994.…”
Section: Discussionmentioning
confidence: 67%
“…Abnormal haemoglobins (Hb) and thalassaemias are some of the most frequently observed hereditary disorders in the world, but especially in the Mediterranean region where Turkey is also located, with clinical profiles that range from asymptomatic to lethal (1)(2)(3). The World Health Organisation (WHO) reports that the frequency of thalassaemias and abnormal Hb carriers is 5.1% with nearly 226 million carriers worldwide (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Within the population of African descent, this prevalence increases to 13.25% (20). The largest number of publications concerning the prevalence of this genetic condition in Latin America comes from Brazil (21,22). For this country, Lervolino et al (23) reported a national prevalence of 9.8% for the carrier genotype; they also reported that there were between 0.8 to 60 cases of newborns with sickle cell disease for every 100,000 live births/year heterogeneously distributed in this population.…”
mentioning
confidence: 97%
“…Por outro lado, a região Norte, considerada a mais carente do país, necessita de maior investimento em saúde pública e em pesquisa, o que se explicita nos estudos escassos oriundos dessa região, um possível indicador de desigualdade (BARBIANI et al, 2016). Em relação às patologias que são abordadas durante o processo de AG, um grande número (n=9) de trabalhos estava focado nas hemoglobinopatias (BARACIOLI et al, 2018;MENESES et al, 2015;SILVA et al, 2015;ACOSTA et al, 2013;FERREIRA et al, 2012;GUIMARÃES et al, 2010;RAMALHO et al, 2007;RAMALHO et al ,2007;DINIZ et al, 2005) e no câncer hereditário (n=6) (PALMERO et al, 2016;ASHTON PROLLA et al, 2015;VIEIRA et al, 2014;SILVA et al, 2013;CUSTÓDIO et al, 2013;PALMERO et al, 2007).…”
Section: Discussionunclassified
“…A necessidade do oferecimento de programas gratuitos de triagem laboratorial, diagnóstico precoce, orientação médica, social e psicológica, com medidas educativas e preventivas para os usuários que convivem com hemoglobinopatias, provavelmente, está relacionada com a formação da população brasileira, que originou-se a partir de uma panmixia étnica, a qual foi composta por povos africanos escravizados (SILVA-FILHO et al, 2011). Essa composição afrodescendente aumentou a prevalência de distúrbios genéticos da hemoglobina (FERREIRA et al, 2012;MOREIRA, 2017) reprodutiva livre e informada. Essa conclusão foi muito bem colocada por Ramalho et al (2007), destacando que o AG tem como objetivo ser primordialmente assistencial e educativo, ou seja, permitir a usuários ou famílias a tomada de decisões reprodutivas consistentes e psicologicamente equilibradas.…”
Section: Discussionunclassified